1999
DOI: 10.1016/s0092-8674(00)80592-9
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog Controls Limb Development by Regulating the Activities of Distinct Transcriptional Activator and Repressor Forms of Cubitus interruptus

Abstract: Hedgehog (Hh) proteins play diverse organizing roles in development by regulating gene expression in responding cells. The Gli homolog Cubitus interruptus (Ci) is involved in controlling the transcription of Hh target genes. A repressor form of Ci arises in the absence of Hh signaling by proteolytic cleavage of intact Ci. We show that this cleavage is essential for limb patterning and is regulated by Hh in vivo. We provide evidence for the existence of a distinct activator form of Ci, which does not arise by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
411
4
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(440 citation statements)
references
References 38 publications
24
411
4
1
Order By: Relevance
“…Zou et al [1997] first reported that overexpressing a constitutively active mutant of BMP type IA receptor induced PTHrP expression in the periarticular perichondrium. Based on these data and studies in many different species showing that BMPs are one of the major targets of Hh signaling [Methot and Basler, 1999], it was proposed that BMPs expressed in the perichondrium can act downstream of Ihh. Indeed, ectopic Ihh expression in chicken embryos induced BMPs 2 and 4 in the perichondrium [Pathi et al, 1999], and BMP activation of BMP receptors in the periarticular perichondrium can increase PTHrP expression.…”
Section: Bone Morphogenic Proteins As Mediators Of Ihh Regulationmentioning
confidence: 99%
“…Zou et al [1997] first reported that overexpressing a constitutively active mutant of BMP type IA receptor induced PTHrP expression in the periarticular perichondrium. Based on these data and studies in many different species showing that BMPs are one of the major targets of Hh signaling [Methot and Basler, 1999], it was proposed that BMPs expressed in the perichondrium can act downstream of Ihh. Indeed, ectopic Ihh expression in chicken embryos induced BMPs 2 and 4 in the perichondrium [Pathi et al, 1999], and BMP activation of BMP receptors in the periarticular perichondrium can increase PTHrP expression.…”
Section: Bone Morphogenic Proteins As Mediators Of Ihh Regulationmentioning
confidence: 99%
“…Hh is required to convert the default Ci 155 to a functional transcriptional activator, as evidenced by clones of cells expressing a non-cleavable form of Ci [65]. These cells accumulate full-length Ci 155 , but do not activate target genes in the absence of Hh stimulation.…”
Section: Cubitus Interruptusmentioning
confidence: 99%
“…The loss of epitope recognition of Ci by the 2A1 antibody, and its relationship to Ci*, are not presently understood. However, it is clear that Ci* is a distinct Ci species, as clones of cells at the A/P boundary that do not express Ci do not activate anterior en [65].…”
Section: Cubitus Interruptusmentioning
confidence: 99%
“…These genes are each expressed in a stripe along the AP compartment boundary, but curiously, stripe widths among the genes varies as does register relative to the AP boundary. This has been explained in terms of differential response of Hhtarget genes to the repressor and activator forms of Ci (Ci-R and Ci-A, respectively) found in anterior compartment cells (Methot and Basler, 1999;Muller and Basler, 2000;Wang and Holmgren, 1999). ptc, for example, has been proposed to respond only to the maximal levels of Ci-A found in cells nearest the AP boundary, while dpp responds to lower levels of Ci-A and also to Ci-R.…”
Section: Activation Of D-h Expressionmentioning
confidence: 99%
“…Ci is expressed specifically in anterior compartment cells and exists in either a cleaved repressor or a full-length activator form (Aza-Blanc et al, 1997). In cells near the AP boundary, Hh prevents cleavage and promotes nuclear entry of the full-length form of Ci, allowing activation of Hh-target genes, such as dpp (Aza-Blanc et al, 1997;Chen et al, 1999;Methot and Basler, 1999;Methot and Basler, 2000;Wang and Holmgren, 1999;Wang and Holmgren, 2000).…”
Section: Introductionmentioning
confidence: 99%